Designing an App for Immunosuppression Adherence and Communication: A Qualitative Approach. (January 2022) - Schick-Makaroff, Kara; Lagendyk, Laura; Foster, Bethany; Lam, Ngan N.; Braam, Branko; Bello, Aminu; Shojai, Soroush; Wen, Kevin
Background: Immunosuppression nonadherence may be the most important factor limiting long-term allograft survival. Objective: Following user-centered design, we explored the essential priorities and preferences of kidney transplant recipients and healthcare providers (HCP) to inform development of a smartphone app to improve immunosuppression adherence and communication. Design: A qualitative descriptive research design was used. Setting: The University of Alberta Hospital adult kidney transplant program in Edmonton, Canada. Participants: Participants were recruited by convenience sampling and included 32 kidney transplant recipients and 11 HCPs. Methods: Seven focus groups (5 with recipients and 2 with HCPs) were conducted to inform app development. Sessions were recorded, and transcripts were coded to elucidate themes. Results: App development to improve adherence was not a priority for HCP. Recipients prioritized choice: that all features be optional. Recipients preferred support while traveling; access to laboratory results; and use by younger or newly transplanted recipients. Both recipients and HCP preferred linkage to pharmacy; and self-management and accountability. For the app to improve communication, HCPs believed the priorities to be addressed included: clarity on scope of app; legal, ethical, and professional obligations; and charting. Both recipients and HCP prioritized HCP workload, and broader medication and health concerns. Healthcare providers preferred tech support; both recipients and HCPs preferred app access for nontransplant HCP. Limitations: Limitations include underrepresentation of physicians, recipients with racial/ethnic diversity, and potential selection bias of transplant recipients who perceived themselves to be adhering to immunosuppression medications. Conclusion: Future research is needed for the app to become a comprehensive, secure platform for broader communication between recipients and HCP, pharmacies, and nontransplant clinicians while streamlining HCP workload.